Stop frowning, it's true: reduced corrugator activity indicates increased positive affect after judging information as true - Stump, Annika; Wüstenberg, Torsten; Voß, Andreas (Cognition & emotion, 2026)
In line with the feelings-as-information theory, a body of research demonstrates more positive (negative) judgments in positive (negative) affective states. Similarly, it has been shown that people who experience positive (negative) affect also tend to judge incoming information as more likely being true (false). Following the argumentation of affect-congruent judgments, we assume that judging information as being true itself possesses a positive affective component. In a truth effect study, we implemented two judgment phases (10 min and 1 week after first exposure) in which 75 participants judged the truth of in total 120 (new and repeated) statements. Addressing the present research question, we assessed spontaneous facial reactions via electromyography after participants provided their truth judgments in each trial. Results reveal corrugator relaxations after judging information as true (vs. false), indicating increased positive affect. Importantly, this finding was unaffected by the repetition status and subjective confidence regarding judgments.
Gesehen am 19.01.2026